HUBUNGAN BERAT BADAN LAHIR RENDAH DENGAN KEJADIAN STUNTING PADA ANAK USIA 10-36 BULAN DI KEPENGHULUAN BAGAN SINEMBAH TIMUR - DESSYKA FEBRIA; ANDI IRFAN; INDRAWATI; GUSMAN VIRGO; TASRIANI (Universitas Pahlawan Tuanku Tambusai, 2022)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition so that children are too short for their age. At present, there are around 162 million children under five years of age experiencing stunting. Several factors that influence the incidence of stunting include birth weight, birth length, gestational age and maternal parenting. Children who experience stunting since childhood will experience problems with slow motor development problems and lower levels of intelligence. The purpose of this study was to determine the relationship between LBW and the incidence of stunting in toddlers 10-36 months in Kepenghuluan Bagan Sinembah Timur. This type of research is quantitative with a cose control approach. Analysis of the data used is univariate and bivariate analysis using chi-square test. The results showed that 33% of children were born with low birth weight and 67% of children were born with normal weight. The results of statistical tests using chi-square analysis showed that the p-value was smaller than 0.05 (0.037 <0.05), meaning that there was a relationship between low birth weight and the incidence of stunting. It is recommended to health workers, cadres and related agencies to be more active and active in providing counseling to mothers to provide nutritious nutritional intake to toddlers